(untitled) (Stato, Chiese e pluralismo confessionale, 2009)
Paper for the International conference held under the auspices of the Minister of Culture of the Slovak Republic “Financing of Churches and Religious Societies in the 21st Century”, in Bratislava 14-15 October 2009, Nitra 16 October 2009. Il contributo è stato segnalato dal Prof. Carlo Cardia.